Social Circus for People with Disabilities: A Video Analysis through the Lens of the MOHO - Bianca A. D. Thompson; Kieran Broome (Occupational Therapy International)
Background. Social circus is a branch of circus that primarily focuses on personal and community development, rather than an elite level of professional artistry required of traditional circus. Social circus engages participants in circus activities such as juggling and acrobatics with therapeutic aims such as building confidence or developing life skills. While there is a growing body of literature around social circus, there is currently limited literature exploring the interface between social circus and occupational therapy theory. Objective. This study is aimed at examining existing examples of social circus for people with disability (via YouTube videos) through the lens of the Model of Human Occupation (MOHO) to consider the link between social circus and contemporary occupational therapy practice. Methods. The study utilised video analysis as the guiding methodology. A two-part qualitative thematic analysis was conducted on transcripts of YouTube video audio and on-screen text, as well as visual analysis of the corresponding imagery. Results. Social circus provides people with disabilities opportunities to actively participate and experience dignity of risk, independence, and autonomy, in a safe and inclusive environment amongst others. As a highly flexible activity (in structure, timing, tasks, outcomes, and environments), social circus accommodated differences in capacities and provided opportunity for the development of skills, both circus-specific and generalisable to everyday life. Social circus allowed people with disability to shape new identities as performers, friends, and members of a community. Conclusion. Social circus offers a unique means for successfully attaining and achieving a wide range of occupational outcomes for people with and without disability across a diverse range of settings. Utilising an occupational therapy lens led to insights around the social circus environments, development of identity and transference of circus skills to everyday tasks and occupations, that were not previously acknowledged in the social circus literature. Our findings support social circus implementation and collaboration within contemporary occupational therapy practice.